Ko wai Au? Who am I? Examining the multiple identities of Māori youth. Issue 3 (15th March 2016) - Faircloth, Susan C.; Hynds, Anne; Jacob, Helen; Green, Clint; Thompson, Patrick
Abstract : In this paper, we present preliminary findings from a unique collaborative research project involving six Deaf Māori rangatahi (youth) in Tāmaki Makaurau (Auckland), Aotearoa New Zealand. This study utilized kaupapa whānau (research family) protocols, established in consultation with two cultural advisory groups within New Zealand and the young people themselves, combined with elements of photovoice methodology, to explore the identities of these youth. Emerging findings highlight the complex nature of these youth's cultural identity as well as specific issues related to access to and participation within te ao Māori (the Māori world). Specific and critical reflections on the research process are also included.